Economics versus Psychology. Risk, Uncertainty and the Expected Utility Theory - Schilirò, Daniele (Journal of Mathematical Economics and Finance; Vol 3 No 1 (2017): JMEF Volume III, Issue 1(4), Summer 2017DO - 10.14505//jmef.v3.1(4).04, 2017)
The present contribution examines the emergence of expected utility theory by John von Neumann and Oskar Morgenstern, the subjective the expected utility theory by Savage, and the problem of choice under risk and uncertainty, focusing in particular on the seminal work “The Utility Analysis of Choices involving Risk” (1948) by Milton Friedman and Leonard Savage to show how the evolution of the theory of choice has determined a separation of economics from psychology.